Power Abuse In Legal Processes Reflected In John Grisham's The Innocent Man: Murder And Injustice In A Small Town Narrative Nonfiction (2006): A Sociological Perspective - Utaminingsih, Yanita; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S, M.Hum (2013)
The major problem of this study is how power abuse in legal processes reflected in John Grisham‟s The Innocent Man: Murder and Injustice in a Small Town. The objective of this study is to analyze the narrative nonfiction based on its structural element and to analyze the narrative nonfiction based on sociological perspective. In analyzing The Innocent Man: Murder and Injustice in a Small Town, the writer uses descriptive qualitative method and sociological perspective. The data sources consist of primary data source and secondary data source. The primary data source is The Innocent Man: Murder and Injustice in a Small Town narrative nonfiction and the secondary data source are taken from some books, websites, and other literary and other matters that support this analysis. The technique of the data collection is library research and the technique of data analysis is descriptive analysis. The outcomes of this study are as follows. First, based on the structural analysis of the narrative nonfiction, Grisham emphasizes that those who are sentenced as guilty are sometimes innocent and are only the victims of power abuse. Second, based on the sociological analysis, there is a close relationship between The Innocent Man: Murder and Injustice in a Small Town narrative nonfiction and social realities of American in the late twentieth and early twenty first centuries.